Pengaruh Bauran pemasaran terhadap keputusan pembelian hijab pada CV Zam Zam Candimulyo Jombang - Ahmad Rowaib Ramadani; Rohmad Prio Santoso (CV. ALIM'SPUBLISHING, 2023)
This study aims to determine the influence of marketing mix on purchasing decisions. This research took the object of CV Zam Zam Candimulyo jombang. The type of research used is quantitative research, the population in this study is customers who buy or order hijab at CV Zam Zam Candimulyo jombang which ranges from 150 people per month with a sample of 60 people. The results showed (1) the influence of the product has a partial influence on the decision to purchase hijab on CV Zam Zam Candimulyojombang (2) the influence of price has a partial effect on the decision to purchase hijab on CV Zam Zam Candimulyo jombang (3) the influence of place has a partial influence on the decision to buy hijab on CV Zam Zam Candimulyo Jombang (4) the influence of promotion has a partial influence on the decision to purchase hijab on CV Zam Zam Candimulyo Jombang (5) the influence of the marketing mix has a simultaneous and significant influence on the decision to purchase hijab on CV Zam Zam Candimulyo Jombang.